A Case of Vulval Extramammary Paget Disease With Dermal Invasion Showing Mucinous Carcinoma. (July 2015) - Asaka, Shiho; Yoshizawa, Akihiko; Sano, Kenji; Uhara, Hisashi; Honda, Takayuki; Ota, Hiroyoshi
Abstract : We report a case of vulval extramammary Paget disease (EMPD) with dermal invasion showing mucinous carcinoma (MC). An 80-year-old woman presented with vulvar itching and pain. A physical examination showed a pigmented vulvar, perianal erythematous plague, and a subcutaneous nodule in the left major labia. No internal malignancy, such as colorectal or genitourinary carcinoma, was identified in any of the clinical examinations. A histological examination of the resected specimen revealed Pagetoid tumor cells that had spread widely through the epidermis and invaded the dermis forming a solid nest with mucous lake-like MC. Immunohistochemical examination revealed that the tumor cells in the epidermis and dermis were positive for CK7, CEA, GCDFP-15, MUC5AC, and MUC2, but negative for CK20, MUC6, and CDX2. Only the invasive component showed overexpression of p53. A diagnosis of primary EMPD with dermal invasion showing MC of the vulva was made. This is an extremely rare diagnosis, and we suggest that immunohistochemical evaluations in addition to systemic work-ups are helpful in distinguishing between these cases and those involving vulvar or perianal skin invasion of underlying colorectal or genitourinary carcinomas, which are referred to as secondary EMPD.